SECONDARY COMPOUNDS RELEASED BY RHIZOSPHERIC BACTERIA EXHIBIT FUNGISTATIC EFFECTS AGAINST PHYTOPATHOGENIC FUNGUS. - Anwar, Sh.; Mahmood, F.; Tahir, N. A.; Salih, G. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of conducted research was to devalute the inhibition effect of metabolites secreted by some  Rhizospheric bacteria on the growth of two pathogenic fungi: Rhizoctonia solani and Fussarium solani, 330 bacteria isolates were obtained from the rhizosphere of  the wheat, tomato, cowpea and Mt. Atlas mastic tree grown in the Sulaimani. Thirty-five isolates were screened for suppression of phytopathogeneic fungus. Results showed that most of these rhizospheric bacteria were have fungistatic potential in different degrees. The highest inhibition of the linear growth of fungi was noted for R. solani and F. solani, by Bacillus cereus LXJ73 (90.41%), Bacillus atropheaus SM-1 (75%) respectively. Six bacterial isolates were selected which have potential effect on the growth of the two studied fungi,  five isolates belonging to the Bacillus genus and one isolate belonging to the genus Klebsiella. these isolates were molecularly confirmed by 16SrRNA, and their activity for inhibiting  fungal growth were studied. The extracted metabolities analysied by Gas chromatography-Mass spectrometry (GC-MS), showing that extracts contain different  volatile organic compounds as  Pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-, 2-Pentanone, 4-hydroxy-4-methyl-, Isosteviol methyl ester,2-methyl-, Butanoic acid, 3-methyl-, 3-Pyrrolidin-2-yl-propionic acid, 9-Octadecenamide, (Z)-, Hexadecane, Tridecane, 2,5-Piperazinedione, 3,6-bis(2-methyl propyl)-, 1,2-Benzenedicarboxylic acid, diisooctyl ester, Acetic acid, Dodecane, beta.-D-Glucopyranose, 1,6-anhydro-, Lauric acid, 2-(hexadecyloxy)-3-(octadecyloxy)propyl ester and cis-Vaccenic acid. The presence of these componuds indicate that all studied Bacillus species and Klebsiella michiganensis M1-3-11having antagonistic activity and they can be used for development of biocontrol agents to reducing the phytopathogenic problems and decreasing mycotoxine  in contaminated crops.